An overview of foreign exchange operation (export procedure) of Prime Bank & comparative analysis with other banks - Ami, Tawhid Rifat (BRAC University, 2012)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.